State-of-the-art of loading and unloading tests for glaucoma: potentialities and informative value - O.S. Myakonkaya; A.S. Sarkisyan; A.V. Seleznev; A.V. Kuroyedov; I.R. Gazizova (РМЖ "Клиническая офтальмология")
O.S.  Myakonkaya1, A.S. Sarkisyan1, A.V. Seleznev2, A.V. Kuroyedov3,4, I.R. Gazizova5 1Volgograd Branch of the S.N. Fedorov NMRC “MNTK “Eye Microsurgery”, Volgograd,   Russian Federation 2Ivanovo State Medical Academy, Ivanovo, Russian Federation 3P.V. Mandryka Military Clinical Hospital, Moscow, Russian Federation 4Pirogov Russian National Research Medical University, Moscow, Russian Federation 5N.P. Bekhtereva Institute of the Human Brain, St. Petersburg, Russian Federation Prevention of blindness and low vision resulting fr om the progression of glaucomatous optic neuropathy (GON) depends mainly on the early diagnosis of glaucoma. Loading and unloading tests which create conditions for intraocular pressure (IOP) fluctuations are important for the early diagnosis of glaucoma. Stress tests for glaucoma lead to a short-term IOP rise and help identify symptoms that are questionable under normal conditions. Stress tests include water-drinking test, position test, dark room test, dentation test, pharmacological mydriasis, corticosteroid provocative test, etc. Unloading tests are reasonable if the IOP level is the upper normal lim it or slightly higher. Unloading tests include glyceryl ascorbate test, test with acetazolamide, and instillations of IOP-lowering medications (e.g., M-cholinomimetic or prostaglandin analog). Visual changes accompanying loading and unloading tests are recorded by visual acuity measurement, IOP measurement (tono metry and tonography, visual field testing (campimetry, angioscotometry), adaptometry, retinal tomography, and electrophysiology (visually evoked potentials). Studies are currently underway to develop novel modifications of diagnostic tests using modern high-tech controlling tools. These advances increase the informative value of these tests which are relevant for both early diagnosis and stabilization of glaucoma course. This review article summarizes currently available data on the informative value of loading and unloading tests. Keywords: glaucoma, intraocular pressure, loading tests, unloading tests, early diagnosis of glaucoma. For citation:  Myakonkaya O.S., Sarkisyan A.S., Seleznev A.V. et al. State-of-the-art of loading and unloading tests for glaucoma: potentialities and informative value. Russian Journal of Clinical Ophthalmology. 2021;21(3):153–158 (in Russ.). DOI: 10.32364/2311-7729-2021-21-3-153-158.